The Impact of Alcohol Use Disorder on Tuberculosis: A Review of the Epidemiology and Potential Immunologic Mechanisms - Wigger, Gregory W.; Bouton, Tara C.; Jacobson, Karen R.; Auld, Sara C.; Yeligar, Samantha M.; Staitieh, Bashar S. (Frontiers in Immunology, 2022)
Globally, an estimated 107 million people have an alcohol use disorder (AUD) leading to 2.8 million premature deaths each year. Tuberculosis (TB) is one of the leading causes of death globally and over 8% of global TB cases are estimated to be attributable to AUD. Social determinants of health such as poverty and undernutrition are often shared among those with AUD and TB and could explain the epidemiologic association between them. However, recent studies suggest that these shared risk factors do not fully account for the increased risk of TB in people with AUD. In fact, AUD has been shown to be an independent risk factor for TB, with a linear increase in the risk for TB with increasing alcohol consumption. While few studies have focused on potential biological mechanisms underlying the link between AUD and TB, substantial overlap exists between the effects of alcohol on lung immunity and the mechanisms exploited by Mycobacterium tuberculosis (Mtb) to establish infection. Alcohol misuse impairs the immune functions of the alveolar macrophage, the resident innate immune effector in the lung and the first line of defense against Mtb in the lower respiratory tract. Chronic alcohol ingestion also increases oxidative stress in the alveolar space, which could in turn facilitate Mtb growth. In this manuscript, we review the epidemiologic data that links AUD to TB. We discuss the existing literature on the potential mechanisms by which alcohol increases the risk of TB and review the known effects of alcohol ingestion on lung immunity to elucidate other mechanisms that Mtb may exploit. A more in-depth understanding of the link between AUD and TB will facilitate the development of dual-disease interventions and host-directed therapies to improve lung health and long-term outcomes of TB.